2011
DOI: 10.1021/pr2004067
|View full text |Cite
|
Sign up to set email alerts
|

Screening Novel Biomarkers for Metabolic Syndrome by Profiling Human Plasma N-Glycans in Chinese Han and Croatian Populations

Abstract: N-glycans play an essential role in biological process and are associated with age, gender, and body mass parameters in Caucasian populations, whereas no study has been reported in Chinese populations. To investigate the correlation between N-glycan structures and metabolic syndrome (MetS) components, we conducted a population-based study in 212 Chinese Han individuals. The replication study was performed on 520 unrelated individuals from a Croatian island Korčula. The most prominent observation was the consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 40 publications
1
44
0
Order By: Relevance
“…The results from our previous study suggested that N- glycosylation of plasma proteins is affected by both age and sex, and that changes in the levels of glycan features can be associated with metabolic syndrome components including BMI, SBP, DBP, and fasting plasma glucose simultaneously. 31 The present data suggested that blood pressures are associated with individual variation in the extent of fucosylation, the degree of branching, levels of sialylation, and levels of glycosylation. Individual variation in IgG glycome composition is very high.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The results from our previous study suggested that N- glycosylation of plasma proteins is affected by both age and sex, and that changes in the levels of glycan features can be associated with metabolic syndrome components including BMI, SBP, DBP, and fasting plasma glucose simultaneously. 31 The present data suggested that blood pressures are associated with individual variation in the extent of fucosylation, the degree of branching, levels of sialylation, and levels of glycosylation. Individual variation in IgG glycome composition is very high.…”
Section: Discussionmentioning
confidence: 49%
“…Based on our previously publication, in which plasma N -Glycan G0 is associated with SBP in Chinese Han and Croatian populations ( r  = 0.194 and 0.314, respectively), 31 the sample size of each group was estimated to be 538 using StatsToDo (http://www.statstodo.com/SSizCorr_Pgm.php) at the significance level of 0.05/23/2 and power of 90%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of suitable size (n Ͼ 200) have performed this to various degrees, finding plasma N-glycans to be highly associated with e.g. age, sex, inflammation, body mass index (BMI), cholesterol and lipid levels (17)(18)(19)(20)(21)(22)(23)(24). However, these studies have either been performed on single proteins, immunoglobulin G (IgG) being a particularly wellstudied example, or predominantly by methods of liquid chromatographic and electrophoretic separation (e.g.…”
mentioning
confidence: 99%
“…The SHSQ-25 has proved to be a reliable and valid instrument for measuring sub-health status in urban Chinese [2]. The progress of a combined genomics and glycomics study for screening biomarkers and exploring SHS as a preventive tool for non-communicable disease control and management will be presented [3]. …”
mentioning
confidence: 99%